2019
DOI: 10.1111/hsc.12839
|View full text |Cite
|
Sign up to set email alerts
|

What approaches to social prescribing work, for whom, and in what circumstances? A realist review

Abstract: The use of non‐medical referral, community referral or social prescribing interventions has been proposed as a cost‐effective alternative to help those with long‐term conditions manage their illness and improve health and well‐being. However, the evidence base for social prescribing currently lags considerably behind practice. In this paper, we explore what is known about whether different methods of social prescribing referral and supported uptake do (or do not) work. Supported by an Expert Advisory Group, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
282
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(334 citation statements)
references
References 79 publications
8
282
2
Order By: Relevance
“…Many other staff members in a medical practice have the opportunity to influence patients, and may have more time than the physicians, thus future efforts would benefit from the engagement of all staff members. This is consistent with a growing interest in social prescribing and use of 'link workers' [68,69]. For future trials, it would be beneficial to have a more proactive discussion with the practice staff to ensure that they identify a small cohort over 2-3 weeks prior to the commencement of a specific, time-limited programme.…”
Section: Motivation For Joining and Maintaining Engagementmentioning
confidence: 58%
“…Many other staff members in a medical practice have the opportunity to influence patients, and may have more time than the physicians, thus future efforts would benefit from the engagement of all staff members. This is consistent with a growing interest in social prescribing and use of 'link workers' [68,69]. For future trials, it would be beneficial to have a more proactive discussion with the practice staff to ensure that they identify a small cohort over 2-3 weeks prior to the commencement of a specific, time-limited programme.…”
Section: Motivation For Joining and Maintaining Engagementmentioning
confidence: 58%
“…A previous realist review by Husk et al. [15] proposed a model for understanding social prescribing more generally, generating statements about enrolment, engagement and completion of activities. Our review has a more specific focus on the link worker role, because these individuals have been identified as key to social prescribing delivery and are being implemented across primary care in England. It sought to answer the following questions:…”
Section: Introductionmentioning
confidence: 99%
“…We used the number of times patients attended the health advice and navigation service during the three months following their initial visit (henceforth described as the number of return visits) as a proxy for patient adherence to it within the observation period. A similar understanding of patients' adherence to such services has been used by other authors in the eld of social prescribing, including 22 [22] and 13 [13]. As our observation period, we used the mean time between patients' initial and last visit in our sample, which was 3 months.…”
Section: Measures Dependent Variablementioning
confidence: 99%
“…To date, research on social prescribing schemes has focused primarily on the English NHS and yielded mixed results regarding their effectiveness and e ciency in improving patient outcomes and reducing GP workload [8,[14][15][16]. However, despite this inconclusive evidence, there is a consensus that any positive effects of referring patients to sources of support in the community can only be expected if patients show ongoing involvement with (i.e., adhere to) them [13,17]. Indeed, studies have reported that the likelihood of achieving positive health-related outcomes increases with the frequency with which a patient uses such services [18][19][20][21].…”
mentioning
confidence: 99%
See 1 more Smart Citation